PEMBELAJARAN MODEL CIRCUIT TRAINING UNTUK MENINGKATKAN KOMPETENSI GRAMATIKAL-LEKSIKAL MAHASISWA BAHASA JERMAN - Rosyidah Rosyidah (Fakultas Sastra Universitas Negeri Malang, 2010)
This article reports on a research aimed at improving the students’ grammatical-lexical competence using learning model circuit training. The subjects were the students of the German Department who took part in the lecture Struktur und Wortschatz 1 Off AA in 2009. The results show that the process consists of four main phases: motivation, going around, training, and presenting; and the ac- tions had the effects: all students were totally active and75 % of the students could present the learning materials correctly, the average point at the end of the second cycle (70,58) can be regarded as successful